Study on the Effect of Water–Binder Ratio on the Carbonation Resistance of Raw Sea Sand Alkali-Activated Slag Concrete and the Distribution of Chloride Ions after Carbonation - Yan Wu; Sixiang Kang; Feng Zhang; Haisheng Huang; Haojie Liu; Jianbin Zhang; Hongze Li; Weihong Li; Zhou Zheng; Wenda Wu (Buildings, 2024)
The excessive extraction of river sand has led to significant ecological issues. Moreover, the environmental impact and resource demand of cement production have increasingly turned the spotlight on sea sand as a viable alternative due to its abundance and ease of extraction. Concurrently, alkali-activated binders, a novel type of low-carbon cementitious material, have gained attention for their low energy consumption, high durability, and effective chloride ion fixation capabilities. However, they are susceptible to carbonation. Introducing a controlled sea sand amount can raise the materials’ carbonation resistance, although carbonation may raise the concentration of free Cl− within the structure to levels that could risk the integrity of steel reinforcements by accelerating corrosion. In this context, the current study investigates sea sand alkali-activated slag (SSAS) concrete prepared with varying water–binder (W/B) ratios to evaluate its impact on flowability, mechanical strength, performances, and chloride ion distribution post-carbonation. The results demonstrate that the mechanical property of SSAS concrete diminishes as the water-to-binder ratio increases, with a more pronounced reduction observed. The depth of carbonation in mortar specimens also rises with the W/B ratio, whereas the compressive strength post-carbonation initially decreases before showing an increase as carbonation progresses. Furthermore, carbonation redistributes chloride ions in SSAS, leading to a peak Cl− concentration near the carbonation front. However, this peak amplitude does not show a clear correlation with changes in the W/B ratio. This study provides a theoretical foundation for employing sea sand and alkali-activated concrete.